Properties of experimental copper-aluminiumnickel alloys for dental post-and-core applications - Apiwat Rittapai (2018)
PURPOSE: This study aimed to develop a copper-aluminium-nickel alloy which has properties comparable to that of dental alloys used for dental post and core applications with the reasonable cost. MATERIALS AND METHODS: Sixteen groups of experimental copper alloys with variants of 3, 6, 9, 12 wt% Al and 0, 2, 4, 6 wt% Ni were prepared and casted. Their properties were tested and evaluated. The data of thermal, physical, and mechanical properties were analyzed using the two-way ANOVA and Tukey's test (α=0.05). The alloy toxicity was evaluated according to the ISO standard. RESULTS: The solidus and liquidus points of experimental alloys ranged from 1023°C to 1113°C and increased as the nickel content increased. The highest ultimate tensile strength (595.9 ± 14.2 MPa) was shown in the Cu-12Al-4Ni alloy. The tensile strength was increased as the both elements increased. Alloys with 3-6 wt% Al exhibited a small amount of 0.2% proof strength. Accordingly, the Cu-9Al-2Ni and Cu-9Al-4Ni alloys not only demonstrated an appropriate modulus of elasticity (113.9 ± 8.0 and 122.8 ± 11.3 GPa, respectively), but also had a value of 0.2% proof strength (190.8 ± 4.8 and 198.2 ± 3.4 MPa, respectively), which complied with the ISO standard requirement (>180 MPa). Alloys with the highest contents of nickel (6 wt% Ni) revealed a widespread decolourisation zone (5.0-5.9 mm), which correspondingly produced the largest cell response, equating positive control. CONCLUSION: The copper alloys fused with 9 wt% Al and 2-4 wt% Ni can be considered for a potential use as dental post and core applications. © 2014 The Korean Academy of Prosthodontics.